IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB DROP-OUT ARV PADA PENDERITA TB-HIV DI KELOMPOK DUKUNGAN SEBAYA ARJUNA SEMARANG - Sifa Fauziah; Kusyogo Cahyo; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2019)
HIV / AIDS is a disease caused by the HIV virus which causes a decrease in the immune system. Decreasing the immune system makes it easier for other diseases to attack the body. Tuberculosis is a disease that is most often suffered by someone who is infected with the HIV virus because the nature of the disease that is easily transmitted is supported by the body's condition with low immunity. Therefore, to improve the immune system the body of a person with HIV is required to consume ARV for life. Consumption of antiretroviral drugs for a lifetime causes a person to experience burnout, so dropping out or dropping from taking antiretroviral. The purpose of this study was to identify the factors that cause drop-out of ARV in patients with TB-HIV in the Arjuna Peer Support Group Semarang. This type of research is qualitative research with in-depth interviews. The population studied were 7 research subjects who were members of the Peer Support Group and 2 subjects were triangulation. Factors identified as causing ARV drop-outs in TB-HIV patients include knowledge, attitudes towards ARV treatment, side effects of ARVs, access to health services, health care facilities, service satisfaction from health workers, family support, partner support, community support, support from health workers, and support from peer support groups.